Hydrolysis of Tetravalent Cerium for a Simple Route to Nanocrystalline Cerium Dioxide: An In Situ Spectroscopic Study of Nanocrystal Evolution. Issue 23 (29th April 2013) - Ikeda‐Ohno, Atsushi; Hennig, Christoph; Weiss, Stephan; Yaita, Tsuyoshi; Bernhard, Gert
Abstract Despite the rapid developments in recent nanocrystal research and their expanding applications, the evolution mechanism of nanocrystals remains veiled for the most part due to the lack of appropriate analytical techniques. Here we demonstrate one promising multi‐spectroscopic approach for the in situ investigation of nanocrystal evolution. That is, the formation of nanocrystalline cerium dioxide (NC‐CeO2) has been probed by dynamic light scattering (DLS), X‐ray absorption spectroscopy (XAS) and high‐energy X‐ray scattering (HEXS). The obtained results indicate that the fine colloidal particles of NC‐CeO2 are formed in an acidic aqueous solution simply through the hydrolysis of the initial precursor of small oligomer CeIV species. This information on how NC‐CeO2 evolves is fundamental to simplifying and alleviating the synthetic strategy for NC‐CeO2 production.